Development of Interactive Learning Media with a Wordwall Platform to Improve Students' Mathematical Divergent Thinking Skills - Carissa Aprilia; Netriwati Netriwati; Siska Andriani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
Mathematical divergent thinking ability is one of the important skills of the 21st century that plays a role in developing students' problem-solving abilities. However, the results of pre-research indicate that students still have difficulty in linking mathematical concepts to real situations and consider mathematics as a difficult subject. This condition indicates the need for innovative, interactive, and interesting learning media to stimulate students' divergent thinking abilities. This study aims to develop a web-based interactive learning media Wordwall that is feasible, interesting, and effective in improving students' mathematical divergent thinking abilities in arithmetic and geometric sequences. This study uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were grade X students of SMA Ma'arif NU 5 Purbolinggo. Data were collected through interviews, questionnaires, and tests with a One Group Pretest-Posttest design. Data analysis was carried out descriptively quantitatively through feasibility, attractiveness, and effectiveness tests with N-Gain calculations. The results of the study showed that the developed media was declared feasible with an assessment of 90.17% from material experts, 97.2% from test experts, and 90.625% from media experts, with a validation of the media's feasibility reaching 96.42%. Student responses reached 92% with a very interesting category, and the N-Gain analysis of the posttest results showed an increase in the average score of students compared to the pretest with an N-Gain value of 0.53 in the small group test and 0.62 in the large group in the "Medium" category. This study recommends the Wordwall web as an innovative learning medium to foster creativity and improve divergent thinking skills.